TRADE AND ECONOMIC RELATIONS BETWEEN RUSSIA AND THE KOKAND KHANATE (SECOND HALF OF THE 18TH CENTURY FIRST HALF OF THE 19TH CENTURY) (International journal of artificial intelligence, 2026)
This article analyzes the evolution of trade and economic relations between the Russian Empire and the Kokand Khanate from the mid-18th century to the mid-19th century. During this period, the Kokand Khanate emerged as a significant political and economic power in Central Asia, particularly within the Fergana Valley. The research explores the dynamics of commodity exchange, the role of merchant classes, and the strategic importance of trade routes connecting Russia with Western China through Kokand. The study highlights how economic interests-driven by Russia’s industrial revolution and its need for raw cotton-laid the groundwork for deeper diplomatic and eventually political involvement in the region.